ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PENGECATAN POWDER COATING MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN METODE MIN-MAX - Zahra Putri Deftya (2021)
The company expects that the planning for controlling the inventory of raw materials owned can run well so that the production process does not experience obstacles such as the lack of raw materials needed and delays in providing requests to consumers. Control of raw materials set by PT XYZ still has not implemented control of raw material inventory. The problem faced by PT XYZ is that the company does not have a safety stock that can be used when raw materials are running low, demand is fluctuating every month which makes the company have to control powder coating raw materials so that raw material orders can be fulfilled. The purpose of this study is to determine the amount of raw materials needed by the company for the following year based on the forecasting method Single Exponential Smoothing, Linear Regression, Moving Average, Exponential Smoothing with Trend, Additive Decomposition based on the smallest MAD; To determine the optimal total cost of raw material inventory using the Economic Order Quantity (EOQ) method and the Min-Max method. ; To determine the comparison of optimal raw material inventory control results between the Economic Order Quantity (EOQ) method and the Min-Max method. Based on these problems, PT. XYZ needs to control the raw materials that will be used in the production process. The EOQ method and the Min-Max method consider the overall costs, in the EOQ method and the Min-Max method there is also a Re-Order Point calculation which means the reorder point and also Safety Stock which means safety stock. The total cost according to company policy in the period February 2020 - January 2021 is Rp. 490,471,000. According to the EOQ Method in the period February 2021 - January 2022, Rp. 476,821,654 and according to the Min-Max method of Rp. 477,922,860. it can be concluded that the EOQ method is more economical because it costs less. The frequency of orders according to company policy is 24 times a year or 2 times a month, while according to the EOQ method, the frequency of orders is 3 times and the Min-Max method is 4 times. Safety stock uses the EOQ method of 12 boxes of paint and uses the Min-Max method of 10 boxes of paint with the aim that the company can handle stockput so that it does not interfere with the production process. Keywords: Forecasting,EOQ,Min-Max